Osiński poznański - Ratajczakowa, Dobrochna; Kalemba-Kasprzak, Elżbieta; Ewa Guderian-Czaplińska, Ewa Guderian-Czaplińska; Przybylski, Ryszard K. (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is a record of a seminar meeting devoted to the memory of professor Zbigniew Osiński, an outstanding theatrologist, first director of the Grotowski Institute in Wrocław, a scholar interested in the works of Juliusz Osterwa, Jerzy Grotowski, Gardzienice Theater and Tadeusz and Irena Byrski’s theatre; researcher of the Oriental theatre reception in Poland. The seminar was organized to commemorate the first death anniversary of the Professor whose scientific path began to take shape in Poznań where he worked until 1970. The record of the meeting reflects its course: in the first part, three short speeches were given: – Professor Dobrochna Ratajczakowa talks about the beginnings of Zbigniew Osiński’s career as a researcher, Professor Elżbieta Kalemba-Kasprzak – about the ‘practice of humanities’ in a specific Poznań way, and professor Ryszard K. Przybylski – about the famous article that used information theory tools written by Balcerzan and Osiński. The second part is devoted to the memories of and reflections on the artistic and scientific activity of Professor Osiński in Poznań. Among the guests of the seminar were Professor Edward Balcerzan, Lech Raczak, Piotr Frydryszek, Janina Karasińska – friends and co-workers of Professor Osiński.